Monitoring Air Quality in Kathmandu with Trend and Public Health Risks - Sah Telee, Lal Babu; Chaudhary, Arun Kumar; Yadav, Umesh Kumar; Karki, Murari (Journal of Nepalese Management Academia, 2024)
Air quality in Kathmandu, Nepal, has become an increasingly critical issue, posing significant risks to both public health and the environment. This study analyzes air quality level, the sources, patterns, and health impacts of air pollution in the Kathmandu Valley. This study has a particular focus on particulate matter PM2.5, PM10 and TSP. Air pollution in Kathmandu exhibits strong seasonal variations, with high concentrations of pollutants during the winter months (particularly January to April) and lower concentrations during the summer (June to August), likely due to monsoon rains., particularly during the winter months when temperature inversions trap pollutants near the surface. Using air quality data from local monitoring stations, this study assesses the extent of pollution in Kathmandu and identifies the trend and the future air condition. The findings highlight the urgent need for effective policy interventions, public awareness campaigns, and enhanced monitoring systems to mitigate the impact of air pollution on public health and the environment. The paper concludes with recommendations for strategies to improve air quality, including stricter emission standards, increased use of cleaner technologies, and community-based initiatives.